Hymenolepis diminuta and Rodentolepis nana (Hymenolepididae: Cyclophyllidea) in urban rodents of Gran La Plata: association with socio-environmental conditions - Fitte, Bruno; Robles, Maria del Rosario; Dellarupe, Andrea; Unzaga, Juan Manuel; Navone, Graciela Teresa (Journal of Helminthology)
The aim of this survey was to study two Hymenolepididae species in urban rodents, Rattus rattus and Rattus norvegicus, and to analyse factors that favour their presence in the environment and pose a sanitary risk. Hymenolepis diminuta and Rodentolepis nana were found in R. rattus and R. norvegicus in different proportions. Values of prevalence, mean abundance and mean intensity were recorded, and new morphometric characters were described, adding to previously known information. No significant differences were found. However, the results revealed that there is a tendency for these parasites to develop in areas with deficient socio-structural conditions and in water bodies. This study thereby shows that certain areas on the periphery of the Gran La Plata favour the existence of rodents, which act as sentinels of zoonotic diseases, and stresses the need to take action to minimize them in order to avoid putting human and animal health at risk. Fil: Fitte, Bruno. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Robles, Maria del Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Dellarupe, Andrea. Universidad Nacional de la Plata. Facultad de Ciencias Veterinarias. Departamento de Epizootiología y Salud Pública. Laboratorio de Inmunoparasitología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Unzaga, Juan Manuel. Universidad Nacional de la Plata. Facultad de Ciencias Veterinarias. Departamento de Epizootiología y Salud Pública. Laboratorio de Inmunoparasitología; ...